BULLYING IN HIGHER EDUCATION: A LITERATURE REVIEW - Cross, Taron (Acta Scientiae et Intellectus, 2024)
This paper reviews literature involving bullying in higher education. Bullying is an undesired, repeated behavior that is intimidating. One person is performing the behavior while one is receiving the behavior who is better known as the victim. Bullying is seen often when elementary, middle, and high schools are being studied. Higher education is overlooked in this area due to belief that bullying decreases as people get older. Research has shown this is not the case due to adult bullying still being a problem in today’s society. This warrants a review of literature to show what research has been done in higher education and what gaps are still problematic in this area. Bullying can take place between students, educators, or administration. Common areas that have shown up in the literature are types of bullying, higher education environment, online classrooms, cyberbullying, victim’s responses, and prevention. Bringing in the research in higher education can help with prevention as well as help to the victims.